Channel interleaver design and performance analysis for ultrasonic through-metal communication - Linsen XU; Wei YANG; Hongxian TIAN (Tongxin xuebao)
Aiming at the problem that the UTM channel can produce successive error bits, a multiple input channel interleaver for UTM communication was proposed.By taking advantages of the grouping idea in multiple input interleaver and the periodic oscillation characteristic of the power gain in the UTM channel, encoded bits were first divided into several groups so that error probabilities of bits in each group varied smoothly.And then, the shift operation and the rectangular interleaver were applied to encoded bits in each group.This not only ensured that interleaved bits in the same group were dispersed into different oscillation cycles, which avoided that the successive bits suffer the high error probability, but also maintained the original bit position sequences, which reduced the influence of UEP.Approximate BER performances for the random interleaver and the proposed interleaver were analyzed and verified by simulation.Simulation results indicate that the proposed interleaver increases the frequency diversity of the UTM communication system and has a lower BER than the random interleaver at high SNR.